The role of user-centered AR instruction in improving novice spatial cognition in a high-precision procedural task. (January 2021) - Wang, Zhuo; Bai, Xiaoliang; Zhang, Shusheng; Billinghurst, Mark; He, Weiping; Wang, Yang; Han, Dong; Chen, Gong; Li, Jianghong
Abstract: AR instruction is a kind of virtual information presented on a human–computer interface. It allows users to view the geometric state, spatial relationship, operation method, and other information involved in the physical task, to form the spatial cognition of the current interaction process. At present, AR instructions cannot support high-precision procedural tasks. The reason is that the existing research work is to use visual elements to express the spatial relationship of physical tasks, without considering transforming the long-term accumulated potential experience of advanced users into a series of effective visual features and interaction modes, to promote the new users to quickly conceive the task intention. In this paper, a user-centered AR instruction(UcAI) is defined and tested for the first time in a procedural task. The control experiment and behavior analysis of 30 participants designing two tasks with different operation precision show that UcAI is more beneficial to improve the user's spatial cognitive ability than conventional AR instruction. Especially in the high-precision operation task, UcAI plays an important role. Our research results have a certain guiding significance for advanced AR instruction design, which extends AR technology to physical tasks with high cognitive complexity.